THE POTENTIOMETRIC UREA BIOSENSOR USING CHITOSAN MEMBRANE - Ani Mulyasuryani; Anna Roosdiana; Arie Srihardyastutie (Indonesian Journal of Chemistry, 2010)
Potentiometric urea biosensor development is based on urea hydrolysis by urease resulted CO2. The biosensor is used chitosan membrane and the H3O+ electrode as a transducer. The research was studied of effecting pH and membrane thickness to the biosensor performance. The best biosensor performance resulted at pH = 7.3 and 0.2 mm of membrane thickness. The biosensor has a Nerntian factor 28.47 mV/decade; the concentration range is 0.1 up to 6.00 ppm; and the limit of detection is 0.073 ppm. The response time of this biosensor is 280 seconds, efficiency 32 samples and accuracy 94% up to 99%.